Soluble peptide–MHC monomers cause activation of CD8(+) T cells through transfer of the peptide to T cell MHC molecules - Ge, Qing (The National Academy of Sciences, 2002)
T cell receptor (TCR)-mediated activation of CD4(+) T cells is known to require multivalent engagement of the TCR by, for example, oligomeric peptide–MHC complexes. In contrast, for CD8(+) T cells, there is evidence for TCR-mediated activation by univalent engagement of the TCR. We have here compared oligomeric and monomeric L(d) and K(b) peptide–MHC complexes and free peptide as stimulators of CD8(+) T cells expressing the 2C TCR. We found that the monomers are indeed effective in activating naïve and effector CD8(+) T cells, but through an unexpected mechanism that involves transfer of peptide from soluble monomers to T cell endogenous MHC (K(b)) molecules. The result is that T cells, acting as antigen-presenting cells, are able to activate other naïve T cells.